Matrix assisted autologous chondrocyte transplantationfor cartilage treatment: A systematic review. Issue 2 (February 2013) - Kon, E.; Filardo, G.; Di Matteo, B.; Perdisa, F.; Marcacci, M.
Abstract : Objectives: Matrix-assisted autologous chondrocyte transplantation (MACT) has been developed and applied in the clinical practice in the last decade to overcome most of the disadvantages of the first generation procedures. The purpose of this systematic review is to document and analyse the available literature on the results of MACT in the treatment of chondral and osteochondral lesions of the knee. Methods: All studies published in English addressing MACT procedures were identified, including those that fulfilled the following criteria: 1) level I-IV evidence, 2) measures of functional or clinical outcome, 3) outcome related to cartilage lesions of the knee cartilage. Results: The literature analysis showed a progressively increasing number of articles per year. A total of 51 articles were selected: three randomised studies, ten comparative studies, 33 case series and five case reports. Several scaffolds have been developed and studied, with good results reported at short to medium follow-up. Conclusions: MACT procedures are a therapeutic option for the treatment of chondral lesions that can offer a positive outcome over time for specific patient categories, but high-level studies are lacking. Systematic long-term evaluation of these techniques and randomised controlled trials are necessary to confirm the potential of this treatment approach, especially when comparing against less ambitious traditional treatments.